Phylogenetic relationships of Culex (Culex) species (Diptera, Culicidae) from Argentina based on morphological characters - Laurito, Magdalena; Almirón, Walter R. (Zootaxa, 2013)
The purpose of this study was for the first time to establish phylogenetic hypotheses among Culex (Culex) species from Argentina, and to evaluate the relationships of this subgenus with subgenera Phenacomyia and Phytotelmatomyia. We em-ployed maximum parsimony to analyse morphological characters derived from the morphology of the adult, pupal and larval stages. More than 30 figures, including photographs, illustrating 87 characters are provided. The cladistic analysis of 61 terminal taxa and 95 characters was undertaken, under implied weighting method, with a range of K values from 6 to 9. Three unstable taxa were detected therefore a reduced strict consensus tree was created. The subgenus Culex appears polyphyletic relative to subgenus Oculeomyia. The internal classification of subgenus Culex is shown to be chaotic; the Pipiens Group is polyphyletic relative to the Sitiens and Coronator Groups, the latter being polyphyletic with respect to the Pipiens Group. Phylogenetic analysis combining characters provided by morphology and molecular sources are need-ed to interpret more fully the relationships in the group.